A Retrospective Study of Pathology in Bats Submitted to an Exotic and Zoo Animal Diagnostic Service in Georgia, USA (2008–2019). (May 2021) - Kirejczyk, Shannon G.M.; Goodwin, Chloe; Gyimesi, Zoltan S.; Zachariah, Trevor T.; Sturgeon, Ginger L.; Armwood, Abigail R.; Frontera-Acevedo, Karelma; Kokosinksa, Anna; Seguel, Mauricio; Fogelson, Susan B.; Burnum, Anne L.; Miller, Doris; et al.
Summary: Pathology records of bats submitted to the University of Georgia from managed care settings were reviewed to identify naturally occurring diseases. Fifty-nine cases were evaluated during an 11-year period (2008–2019), including representatives from four families: Pteropodidae (Yinpterochiroptera), Phyllostomidae, Vespertilionidae and Molossidae (Yangochiroptera). Pathology reports were reviewed to determine the primary pathological process resulting in death or the decision to euthanize. Cases were categorized as non-infectious (34/59; 58%), infectious/inflammatory (17/59; 29%) or undetermined due to advanced autolysis (8/59; 14%). Musculoskeletal diseases and reproductive losses were the most frequent pathological processes. Among the infectious processes identified, bacterial infections of the reproductive and haemolymphatic systems were most frequently observed. The first two reports of neoplasia in small flying foxes ( Pteropus hypomelanus ) are described. Bats under managed care present with a wide range of histopathological lesions. In this cohort, non-infectious disease processes were common.